Simulation method for handling acute injuries to increase knowledge and skills of STIKES Graha Edukasi Makassar students - Rumtili, Tirsa; Thalib, Abdul; Nurhikmah, Nurhikmah; Mustafa, Sri Resky (Innovative Approaches in Health Science Journal, 2024)
Background: injuries are important because they are taught about basic techniques for saving victims from various accidents or daily disasters that are commonly encountered. Objective: To determine the  effect of the simulation method of handling acute injuries on increasing knowledge and skills in  Makassar Graha Education Stikes  Students. Method: Quantitative research method  with Quasi-Experimental  design (pseudo-experiment) with pre-test post test control group design  (pre-post test design) to determine the level of knowledge and skills with simulation methods for acute wound management. Results:  there is an influence of the simulation method on the level of knowledge and skills of STIKES Graha Edukasi Makassar students (p = 0.000). Conclusion: The simulation method of acute wound management effectively increases the knowledge and skills of students of Stikes Graha Edukasi Makassar, with significant improvements in both aspects and proven relationships between simulation methods and increased knowledge, as well as student skills.